Effect of platelet-rich plasma on the healing of mandibular defects treated with fresh frozen bone allograft: a radiographic study in dogs - Messora, Michel R.; Nagata, Maria José Hitomi [UNESP]; Fucini, Stephen E. [UNESP]; Pola, Natalia M. [UNESP]; Campos, Natalia [UNESP]; Oliveira, Guillermo C. V. de [UNESP]; Bosco, Álvaro Francisco [UNESP]; Garcia, Valdir Gouveia [UNESP]; Furlaneto, Flavia A. C. (Allen Press Inc, 2014)
The purpose of this study was to radiographically analyze the effect of autologous platelet rich plasma (PRP) on the healing of fresh frozen bone allograft (FFBA) placed in surgically created resection defects in mandibles of dogs. Bilateral resection defects measuring 1.5 cm x 1 cm were surgically created on the inferior border of the mandible in 10 adult male dogs. The defects were randomly divided into three groups: C, FFBA, and FFBA/PRP. In Group C, the defect was filled by blood clot only. In Group FFBA, the defect was filled with particulate fresh frozen bone allograft. In Group FFBA/PRP, it was filled with particulate fresh frozen bone allograft combined with PRP. At 90 days postoperative, standardized radiographs of the mandibles were obtained and results were quantitatively evaluated. Analysis of digitized radiographs indicated that non-PRP grafts were significantly less dense than the PRP grafts. Group FFBA/PRP also presented a statistically greater mineralized tissue area than Groups C and FFBA. Within the limits of this study, it can be concluded that PRP enhanced the healing of FFBA in resection defects in mandibles of dogs.
Keywords: bone regeneration; growth factors; platelets; bone grafting